Interrupted right-sided aortic arch: performance of umbilical xenograft after primary neonatal corrective surgery - Shahinian, Jasmin H.; Tobler, Daniel; Wolff, Thomas; Grapow, Martin (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Interrupted aortic arch (IAA) associated with right-sided aorta descendens is a rare congenital malformation. We present a case of a female patient who was diagnosed with type B IAA and received primary corrective surgery as a neonate. A bovine umbilical vascular graft was used to establish aortic arch continuity. Thirty-nine years later the same patient presents with graft-dilatation and a distal aneurysm requiring a surgery. This case shows a late complication of a biological xenograft in term of long-term material performance. Moreover, it highlights the necessity for regular follow-ups in order to detect and treat late onset complications respectively.